Design & Fabrication of Automatic Color & Weight-Based Sorting System on Conveyor Belt - Tasnuva Jahan Nuva; Md. Imteaz Ahmed; Sarker Safat Mahmud (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2022)
Object sorting is a basic process that is employed in a variety of disciplines in our daily lives for our convenience. Previously, the sorting operation was done by hand using labor justification. Because product quality does not remain consistent during the typical sorting process, it adds complexity to the segregation of products based on their height, color, size, and weight. This method is also time-consuming and slows down output. To overcome these problems, Low-Cost Automation (LCA) has been implemented in the sorting system, which aims to reduce production time, labor cost, and processing complexity, improve product quality, increase production rate, etc. So, in this project, an effective method has been developed for automatically sorting the object based on color and weight. This method uses a conveyor belt, strain gauge load cell, DC motor, servo motor, TCS 34725 RGB color sensor, LCD, LED, and LDR to identify, separate, and collect the objects according to their color and weight. Arduino is used to controlling all the processes. This work has sorted three types of colors -red, , green, and blue, and the weight of different ranges. Firstly, the weights have been sorted by load cell, and then the desired colors have been sorted by color sensor. A bucket at the end of the conveyor belt can be rotated depending on the signal sent from the Arduino to collect the box. The collecting box has a specific portion in a particular color. Hence, it could be rotated at a specific angle for an exact weight for red, blue, and green colors.